(untitled) (Journal of Dhaka Medical College, 2024)
Background: Postoperative respiratory complications are still a matter of ‘folds in forehead’ for surgeons. Though optimum pre-operative preparation and good surgical technique, we always observe that there are some sorts of post-operative chest complications after major abdominal surgery. Now-a-days, chest physiotherapy is usually advised by the surgeons in the immediate postoperative period. But still it is not in a constructive way. There is no well-documented study regarding the effectiveness of chest physiotherapy in an immediate post-operative period of major upper abdominal surgery. So, this is a time demanding study in this regard. Objectives: To evaluate the effectiveness of chest physiotherapy during the immediate postoperative period among patients undergoing elective major abdominal surgery. Methods: All patients who underwent major abdominal surgery were selected by purposive sampling. Thereafter, they were scrutinized according to eligibility criteria and 100 patients were finalized. Among them, 50 were enrolled under control group and rest 50 were enrolled under study group. This experimental study was conducted in department of Surgery, Dhaka Medical College Hospital, Dhaka, from March 2017 to December 2017. Results: The mean age of the participants in control and study groups were 49.73±15.91 year and 53.77±12.21 year respectively. The female to male ratio in these groups was 1:2.13 and 1:3.17 respectively. Two groups presented similar levels of pain before and after surgery. The group receiving chest physiotherapy presented a lower pain score on the immediate postoperative day. The preoperative spirometry values (expressed as a percentage of the predicted values) were almost similar in two groups and presented average decreases of 20% in FVC, FEV, and PEF on the 14th post-operative day. It was observed that the measurements of oxygen-hemoglobin saturations were different for the control (96.7±1.6 vs 95.2±1.8; p=0.005) and study group (97.3±1.8 vs 94.6±2.5; p=0.03). Respiratory distress was not significantly higher in control group but interestingly there were statistically significant differences observed between the control and study group regarding fever, Surgical site infection (SSI) and mean hospital stay. Conclusion: Chest physiotherapy in major abdominal surgery shows an excellent outcome that accelerates the overall recovery. J Dhaka Med Coll. 2022; 31(2) : 177-181